Voriconazole as a secondary prophylaxis for cryptococcal meningitis during hematopoietic stem cell transplantation. (2021) - Kashima, Emiko; Nagaharu, Keiki; Ino, Kazuko; Sugimoto, Yuka; Fujieda, Atsushi; Kawakami, Keiki; Tawara, Isao
Abstract: Antifungal prophylaxis is crucial for successful hematopoietic stem cell transplantation (HSCT). Maintenance therapy with fluconazole (FLCZ) is generally prescribed as secondary prophylaxis in patients with human immunodeficiency virus infection and non-immunocompromised hosts. However, previous reports have revealed that FLCZ is insufficient as a secondary prophylaxis for cryptococcal infection in HSCT cases. There is no well-established evidence of effective secondary prophylaxis against cryptococcal infection in conditions of severe immunosuppression, such as in HSCT. Herein, we report a case of atypical chronic myeloid leukemia (aCML) presenting with cryptococcal meningitis. A 58-year-old man with progressive leukocytosis and headache was referred to our hospital. Bone marrow biopsy revealed aCML. Because the estimated overall survival was limited, HSCT was indicated. Furthermore, enhanced magnetic resonance imaging and lumbar puncture aided in diagnosing cryptococcal meningitis, which was treated with a combination therapy comprising liposomal amphotericin B and 5-fluorocystine for 28 days. Given the high recurrence rate of cryptococcal meningitis, voriconazole (VRCZ) dose was calculated using the trough concentration of VRCZ in the cerebrospinal fluid. Eventually, HSCT was successfully performed at an appropriate therapeutic range of VRCZ. To the best of our knowledge, there is no case report on HSCT with secondary prophylaxis against cryptococcal meningitis. Our report thus emphasizes the efficacy of VRCZ maintenance therapy as secondary prophylaxis for cryptococcal infection.